Maharashtra, India : Improving Panchayat Service Delivery through Community Score Cards - Murty, J.V.R.; Agarwal, Sanjay; Shah, Parmesh (World Bank, Washington, DC, 2016)
This note summarizes the experiences from a pilot project undertaken by the Tata Institute of Social Sciences (TISS), Mumbai, in partnership with the World Bank-sponsored Jalswarajya Project. The current initiative was one of six pilot projects launched by the South Asia Sustainable Development Department (SASAR) of the World Bank aimed at the application of specific social accountability tools in different contexts of service delivery through the trust fund for Capacity Building and Piloting of Social Accountability Initiatives for Community Driven Development in South Asia.